Novel Insights into the Biotin Carboxylase Domain Reactions of Pyruvate Carboxylase from Rhizobium etli - Zeczycki, Tonya N. (2011)
The catalytic mechanism of the MgATP-dependent carboxylation of biotin in the biotin carboxylase domain of pyruvate carboxylase from R. etli (RePC) is common to the biotin-dependent carboxylases. The current site-directed mutagenesis study has clarified the catalytic functions of several residues proposed to be pivotal in MgATP-binding and cleavage (Glu218 and Lys245), HCO(3)(−) deprotonation (Glu305 and Arg301) and biotin enolization (Arg353). The E218A mutant was inactive for any reaction involving the BC domain and the E218Q mutant exhibited a 75-fold decrease in k(cat) for both pyruvate carboxylation and the full reverse reaction. The E305A mutant also showed a 75- and 80-fold decrease in k(cat) for both pyruvate carboxylation and the full reverse reaction, respectively. While Glu305 appears to be the active site base which deprotonates HCO(3)(−), Lys245, Glu218 and Arg301 are proposed to contribute to catalysis through substrate binding interactions. The reactions of the biotin carboxylase and carboxyl transferase domains were uncoupled in the R353M-catalyzed reactions, indicating that Arg353 may not only facilitate the formation of the biotin enolate, but also assist in coordinating catalysis between the two spatially distinct active sites. The 2.5 and 4-fold increase in k(cat) for the full reverse reaction with the R353K and R353M mutants, respectively, suggests that mutation of Arg353 allows carboxybiotin increased access to the biotin carboxylase domain active site. The proposed chemical mechanism is initiated by the deprotonation of HCO(3)(−) by Glu305 and concurrent nucleophilic attack on the γ-phosphate of MgATP. The trianionic carboxyphosphate intermediate formed reversibly decomposes in the active site to CO(2) and PO(4)(3−). PO(4)(3−) then acts as the base to deprotonate the tethered biotin at the N(1)-position. Stabilized by interactions between the ureido oxygen and Arg353, the biotin-enolate reacts with CO(2) to give carboxybiotin. The formation of a distinct salt bridge between Arg353 and Glu248 is proposed to aid in partially precluding carboxybiotin from reentering the biotin carboxylase active site, thus preventing its premature decarboxylation prior to the binding of a carboxyl acceptor in the carboxyl transferase domain.